Performance analysis of wavelength assignment policies in all-optical networks with limited-range wavelength conversion. - Harai, H.
Previous analytic approaches for all-optical networks have only allowed a random wavelength assignment policy in spite of the fact that network performance can be improved by other wavelength assignment policies such as first-fit wavelength assignment. We develop an approximate analytic method to allow flexible wavelength assignment policies by virtue of a layered-graph approach. Our analysis is also applicable to the networks that wavelength conversion is limitedly provided. By comparing with simulation results, we show that our analytic approach has good accuracies when the number of wavelengths is not large. We also show that our analysis is applicable to general network topologies
Keywords: BPP/M/1/1 queue; Bernouli-Poisson-Pascal queue; Accuracy; All-optical networks; Approximate analytic method; First-fit wavelength assignment; General network topologies; Layered-graph approach; Limited-range wavelength conversion; Network performance; Network routing; Performance analysis; Random wavelength assignment policy; Simulation results; Wavelength assignment policies